#2**+2 **

Consider the equation as two separate equations: \(5x + 3 = 4x - 1\) and \(-(5x + 3) = 4x - 1\)

Now, solve both equations for x as you normally would. Be careful of the negative in the second equation.

BuilderBoi Apr 21, 2023

#3**+1 **

Another way to do it (which is harder in this instance, is to square both sides

\(|5x+3| = 4x - 1\\ 25x^2+30x+9=16x^2-8x+1\\ 9x^2+38x+8=0\\ x=\frac{-38\pm \sqrt{1156}}{18}\\ x=\frac{-38\pm 34}{18}\\ x=\frac{-19\pm 17}{9}\\ x=\frac{-2}{9}\qquad or \qquad x=\frac{-36}{9}\\ x=\frac{-2}{9}\qquad or \qquad x=-4\\ \)

Check both answers in original equation and you will find that one of them is invalid.

So the other one is the answer. :)

Melody Apr 22, 2023